Extracellular RNA in Central Nervous System Pathologies - Tielking, Katharina; Fischer, Silvia; Preissner, Klaus T.; Vajkoczy, Peter; Xu, Ran (Frontiers in Molecular Neuroscience, 2019)
The discovery of extracellular RNA (exRNA) has shifted our understanding of the role of RNA in complex cellular functions such as cell-to-cell communication and a variety of pathologies. ExRNAs constitute a heterogenous group of RNAs ranging from small (such as microRNAs) and long non-coding to coding RNAs or ribosomal RNAs. ExRNAs can be liberated from cells in a free form or bound to proteins as well as in association with microvesicles (MVs), exosomes, or apoptotic bodies. Their composition and quantity depend heavily on the cellular or non-cellular component, the origin, and the RNA-species being investigated. Different forms of exRNA correspond to the distribution and quantity of RNA species inside cells, whereby ribosomal RNA provides the majority of exRNA and miRNAs are predominantly associated with exosomes or MVs. Several studies showed that ribosomal exRNA (rexRNA) constitutes a proinflammatory and prothrombotic alarmin. It is released by various cell types upon inflammatory stimulation and by damaged cells undergoing necrosis or apoptosis and contributes to innate immunity responses. This exRNA has the potential to directly promote the release of cytokines such as tumor necrosis-factor factor-α (TNF-α) or interleukin-6 from immune cells, thereby leading to a proinflammatory environment and promoting cardiovascular pathologies. The potential role of exRNA in different pathologies of the central nervous system (CNS) has become of increasing interest in recent years. Although various exRNA species including both ribosomal exRNA as well as miRNAs have been associated with CNS pathologies, their precise roles remain to be further elucidated. In this review, the different entities of exRNA and their postulated roles in CNS pathologies including tumors, vascular pathologies and neuroinflammatory diseases will be discussed. Furthermore, the potential role of exRNAs as diagnostic markers for specific CNS diseases will be outlined, as well as possible treatment strategies addressing exRNA inhibition or interference.